Awake prone positioning for COVID-19 acute hypoxaemic respiratory failure: a randomised, controlled, multinational, open-label meta-trial. Issue 12 (December 2021) - Ehrmann, Stephan; Li, Jie; Ibarra-Estrada, Miguel; Perez, Yonatan; Pavlov, Ivan; McNicholas, Bairbre; Roca, Oriol; Mirza, Sara; Vines, David; Garcia-Salcido, Roxana; Aguirre-Avalos, Guadalupe; Trump, Matthew W; et al.
Summary: Background: Awake prone positioning has been reported to improve oxygenation for patients with COVID-19 in retrospective and observational studies, but whether it improves patient-centred outcomes is unknown. We aimed to evaluate the efficacy of awake prone positioning to prevent intubation or death in patients with severe COVID-19 in a large-scale randomised trial. Methods: In this prospective, a priori set up and defined, collaborative meta-trial of six randomised controlled open-label superiority trials, adults who required respiratory support with high-flow nasal cannula for acute hypoxaemic respiratory failure due to COVID-19 were randomly assigned to awake prone positioning or standard care. Hospitals from six countries were involved: Canada, France, Ireland, Mexico, USA, Spain. Patients or their care providers were not masked to allocated treatment. The primary composite outcome was treatment failure, defined as the proportion of patients intubated or dying within 28 days of enrolment. The six trials are registered with ClinicalTrials.gov, NCT04325906, NCT04347941, NCT04358939, NCT04395144, NCT04391140, and NCT04477655 . Findings: Between April 2, 2020 and Jan 26, 2021, 1126 patients were enrolled and randomly assigned to awake prone positioning (n=567) or standard care (n=559). 1121 patients (excluding five who withdrew from the study) were included in the intention-to-treat analysis. Treatment failure occurred in 223 (40%) of 564 patients assigned to awake prone positioning and in 257 (46%) of 557 patients assigned to standard care (relative risk 0·86 [95% CI 0·75−0·98]). The hazard ratio (HR) for intubation was 0·75 (0·62−0·91), and the HR for mortality was 0·87 (0·68−1·11) with awake prone positioning compared with standard care within 28 days of enrolment. The incidence of prespecified adverse events was low and similar in both groups. Interpretation: Awake prone positioning of patients with hypoxaemic respiratory failure due to COVID-19 reduces the incidence of treatment failure and the need for intubation without any signal of harm. These results support routine awake prone positioning of patients with COVID-19 who require support with high-flow nasal cannula. Funding: Open AI inc, Rice Foundation, Projet Hospitalier de Recherche Clinique Interrégional, Appel d'Offre 2020, Groupement Interrégional de Recherche Clinique et d'Innovation Grand Ouest, Association pour la Promotion à Tours de la Réanimation Médicale, Fond de dotation du CHRU de Tours, Fisher & Paykel Healthcare Ltd.